Wireless optoelectronic recordings of mandibular and associated head-neck movements in man: a methodological study - Zafar, H.; Eriksson, P.-O.; Nordh, E.; Häggman-Henrikson, B. (Journal of oral rehabilitation, 2000)
Human mandibular movements in space are the result of combined motions of the mandible and the head–neck. They can be simultaneously monitored by an optoelectronic recording technique via markers at different locations on the mandible and on the head. Markers can be attached to the teeth or to the facial skin. Mandibular movements relative to the head can be calculated by one‐ or three‐dimensional (1D and 3D, respectively) mathematical compensation for head movements. The present study analysed mandibular and associated head movements during maximal jaw opening–closing tasks in 10 healthy subjects using a wireless 3D optoelectronic movement recording system. The study aimed to: (i) estimate the soft tissue related displacement of skin‐attached markers at different locations on the face; (ii) compare 1D with 3D mathematical compensation for associated head movements; (iii) evaluate the influence of marker location on the recorded head and mandibular movement amplitudes; and (iv) compare skin‐attached markers with teeth‐attached markers with regard to temporal estimates of recorded mandibular and head movements. Markers were attached to the upper and lower incisors and to the skin of the forehead, nose‐bridge, nose‐tip and chin. Soft tissue related displacement of skin‐attached markers varied between locations. The displacement for the chin marker was larger than that of other markers. The least displacement was found for the nose‐bridge marker. However, relative to mandibular and head movements, respectively, the displacement of the chin marker was of the same order as that of the nose‐bridge marker. The temporal estimates were not significantly affected by displacement of the skin‐attached markers. Markers at different locations on the head and the mandible registered different amplitudes. The mandibular movement patterns calculated by 1D and 3D compensation were not comparable. It is concluded that markers attached to the chin and the nose‐bridge can be reliably used in temporal analyses of mandibular and head movements during maximal jaw opening–closing. With certain limitations, they are acceptable for spatial analyses. Selection of method of marker attachment, marker location, and method of compensation for associated head movements should be based on the aim of the study.